Decoupling between Ti‐in‐zircon and Zr‐in‐rutile thermometry during ultrahigh temperature metamorphism of the Dabie Orogen, China. (25th March 2020) - Lei, Hengcong; Xu, Haijin; Liu, Penglei
Abstract : The Ti‐in‐zircon (TIZ) and Zr‐in‐rutile (ZIR) geothermometers record metamorphic temperatures. In theory, their results should be consistent when zircon and rutile equilibrate as they form. However, we show that these geothermometers were decoupled during ultrahigh temperature (UHT) metamorphism of the Dabie Orogen, China. The TIZ geothermometer records a peak temperature of 927 ± 38°C for the granulite‐facies metamorphism. Rutile occurs as inclusions in UHT metamorphic zircon domains, and they were syn‐crystallised. Rutile records ZIR temperatures of 783 to 798°C. We infer that diffusion of Ti and Zr between zircon and rutile is the main cause of decoupling between the TIZ and ZIR geothermometers. Diffusion of Zr in rutiles is closely related to the distribution of elements, the duration of UHT metamorphism, and rutile grain size.